2020
DOI: 10.3390/ijms21197173
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ketamine on Rodent Fear Memory

Abstract: Ketamine, a multimodal anesthetic drug, has become increasingly popular in the treatment of pain following traumatic injury as well as treatment-resistant major depressive disorders. However, the psychological impact of this dissociative medication on the development of stress-related disorders such as post-traumatic stress disorder (PTSD) remains controversial. To address these concerns, preclinical studies have investigated the effects of ketamine administration on fear memory and stress-related behaviors in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…Accordingly, it was suggested that ketamine is effective when administered before, but not after, exposure to stressors ( McGowan et al, 2017 ). On the other hand, consistent with our results, a number of studies reported a reduction of fear both when ketamine was administered before ( McGowan et al, 2017 , 2018 ; Chen B. K et al, 2020 ) or after stress ( Duclot et al, 2016 ; Girgenti et al, 2017 ; Asim et al, 2020 ; Radford et al, 2020 ), although some inconsistencies were found ( Choi et al, 2020 ). Overall, this suggests that ketamine can affect previously established fear memory, thus improving the recovery from traumatic experiences.…”
Section: Discussionsupporting
confidence: 91%
“…Accordingly, it was suggested that ketamine is effective when administered before, but not after, exposure to stressors ( McGowan et al, 2017 ). On the other hand, consistent with our results, a number of studies reported a reduction of fear both when ketamine was administered before ( McGowan et al, 2017 , 2018 ; Chen B. K et al, 2020 ) or after stress ( Duclot et al, 2016 ; Girgenti et al, 2017 ; Asim et al, 2020 ; Radford et al, 2020 ), although some inconsistencies were found ( Choi et al, 2020 ). Overall, this suggests that ketamine can affect previously established fear memory, thus improving the recovery from traumatic experiences.…”
Section: Discussionsupporting
confidence: 91%
“…Ketamine at high doses interferes with fear memory and extinction consolidation ( Clifton et al, 2018 ; Duclot et al, 2016 ), while lower doses (10 mg/kg) facilitate memory consolidation ( Radford et al, 2018 ). The effects of ketamine on fear memory depend on route of administration as well as dose ( Choi et al, 2020 ). Ketamine at low doses, given intraperitoneally, accelerates FE learning via mTORC1 signaling, a downstream target of BDNF receptor activation ( Girgenti et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is especially important given that ketamine may be an effective treatment of post-traumatic stress disorder [ 106 ], a condition in which patients fail to recover from a traumatic event due to the persistence of the traumatic memory. While preclinical findings with ketamine have so far been inconsistent with regard to the extinction of learned fear [ 107 ], understanding the effects of ( 2R,6R )-HNK on threat-aggravated memory will be an important step toward understanding its potential effectiveness in stress-related disorders and its unique therapeutic mechanism of action.…”
Section: Discussionmentioning
confidence: 99%